Determining Appropriate Policies for Prostitution Reform in Indonesia - Natalis, Aga; Purwanti, Ani; Asmara, Teddy (Journal of Southeast Asian Human Rights, 2023)
In the context of the current efforts that Indonesia is making to alter its prostitution laws, it is of the utmost importance to determine the strategy that will be most effective. The two strategies implemented most are known as harm reduction and harm elimination. This study employs a juridical-normative research method to analyse various plans, weighing the pros and cons of each option and providing recommendations on the most suitable approach for Indonesia. The findings highlight the necessity for an all-encompassing and multi-disciplinary approach, intending to strike a balance between the protection of the rights of sex workers and the reduction of harm done to society. It has been found that a policy of harm reduction may be more appropriate for Indonesia as it recognises the existence of prostitution and works toward addressing the root causes of the problem while simultaneously attempting to lessen the adverse effects of the practice. Keywords: Prostitution Policy, Harm Elimination; Harm Reduction; Prostitution Law; Indonesia